KEPEMIMPINAN KYAI YANG BERORIENTASI PADA IMTAQ DAN IPTEK (Studi Kasus di Pondok Pesantren Wilayatul Ummah Kampung Damai Ponorogo) - Hariadi Hariadi (Institut Agama Islam Ngawi, 2011)
Abstract: This study about kyai leadership and focused on his leadership orientation. Findings show that the leadership ofÂ the kyai is oriented to development of IMTAQ and that completed with IPTEK can produce a leader that has good emotional and spiritual quotient (ESQ). It is recommended that, who are improve their leadership orientation, should improve the quality of IMTAQ and the quality of IPTEK capability.